Phase II trial of utidelone as monotherapy or in combination with capecitabine in heavily pretreated metastatic breast cancer patients. Issue 1 (December 2016) - Zhang, Pin; Tong, Zhongsheng; Tian, Fuguo; Wang, Yongsheng; Yang, Junlan; Li, Weilian; Di, Lijun; Liu, Wei; Tang, Li; Qiu, Rongguo; Xu, Binghe
Abstract Background The treatment of metastatic breast cancer (MBC) remains a great clinical challenge as drug resistance frequently develops. Alternative agents that can overcome drug resistance would offer new therapeutic options. The primary aim of this phase II study was to evaluate the efficacy and safety of utidelone as a monotherapy or in combination with capecitabine in metastatic breast cancer patients previously treated with and resistant to anthracyclines and taxanes. Methods In two open-label, noncomparative clinical studies, patients with metastatic breast cancer who previously received anthracycline- and/or taxane-containing regimens were given (1) 25 to 35 mg/m2 /day intravenously infused utidelone, once daily for 5 days, in combination with 14 days of 2000 mg/m2 capecitabine, divided in two equal daily oral doses or (2) 40 mg/m2 /day intravenously infused utidelone, once daily for 5 days. These regimens were administered per each 21-day treatment cycle, and the maximum of treatment cycles allowed per protocol is 6. Objective response rate (ORR), progression-free survival (PFS), and tolerability were evaluated. Results In the combination study, 33 patients completed a median of 6 cycles of therapy, which was the highest cycles a trial patient could receive under the criteria of the study protocol. Efficacy was evaluated (n  = 32) with an ORR of 42.4 % (FAS, 95 % CI, 26.6, 60.9) and a median PFS of 7.9 (FAS, 95 % CI, 6.1, 9.8) months. The monotherapy study (n  = 63) resulted in an ORR of 28.57 % (FAS, 95 % CI, 18.4, 40.6) and a median PFS of 5.4 (FAS, 95 % CI, 2.9, 9.8) months. In both studies, common toxicities associated with utidelone administration included peripheral neuropathy, fatigue, myalgia, and arthralgia, but the toxicities were limited and manageable. Notably, very mild myelosuppression, low liver and renal toxicities, and very limited gastrointestinal toxic effect were observed, in contrast to other agents in the same class. Conclusions Utidelone showed promising efficacy, tolerability, and advantageous safety profiles in the treatment of patients with advanced anthracycline/taxane-refractory metastatic breast cancer and may offer new treatment options to overcome drug resistance. Trial registration CHiCTR-TRC-13004205, registered on August 15, 2013.